Language Taboos in Social Activities of the Acehnese Community - Vera Wardani; Mujiburrahman Mujiburrahman; Junaidi Junaidi; Usman Usman; Ade Ikhsan Kamil (Andalas International Journal of Socio-Humanities, 2023)
This study aims to describe language taboos in the context of social activities within the Acehnese community. The research design employed is field research, utilizing a qualitative approach. The method employed is descriptive-analytical. The data for this research focus on language taboos within the Acehnese community in the Pidie Regency. The data sources are informants, comprising Acehnese individuals residing in the Pidie Regency, spanning three sub-districts, with a total of 21 informants. Data collection involves structured and unstructured interview techniques, supported by the participant observation method with face-to-face conversations and the baiting technique. The data analysis technique used is qualitative analysis with stages such as selection, description, grouping, and data analysis. The research findings reveal language taboos in the social activities of the Acehnese community as follows: (a) language taboos in hunting activities; (b) language taboos in farming activities; (c) language taboos in carpentry activities; (d) language taboos in trading activities; and (e) language taboos in courtship activities.